2020
DOI: 10.22437/irje.v4i1.7555
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Plights of Nigerians in Diaspora: A Case Study of Nigerians Studying in Malaysian Universities

Abstract: In view of researchers’ personal experiences and report on numerous problems of Nigerians in diaspora, this study investigates the plights of Nigerians in diaspora with specific focus on Nigerians studying in Malaysian universities. In order to select participants for the study stratified, purposive and convenience sampling techniques were used to select 10 Nigerian students from three Malaysian universities, namely Universiti Utara Malaysia (UUM), Universiti Malaya (UM) and Insaniah University College. Instru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Consistent child and maternal mortality rates are avoidable if enough doctors are eagerly available to work. The relationship between the number of medical personnel and mortality rates occurring in Nigeria has been recorded in the extant literature, demonstrating the poor magnitude of the paucity of doctors in Nigeria's healthcare sector (Rufai, Ogunniyi, Salman, Oyeyemi, & Salawu, 2019; Suleiman & Mikail, 2020). The core reason many physicians move outside Nigeria every day is the industry's lack of funding and inadequate salary compared to other developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent child and maternal mortality rates are avoidable if enough doctors are eagerly available to work. The relationship between the number of medical personnel and mortality rates occurring in Nigeria has been recorded in the extant literature, demonstrating the poor magnitude of the paucity of doctors in Nigeria's healthcare sector (Rufai, Ogunniyi, Salman, Oyeyemi, & Salawu, 2019; Suleiman & Mikail, 2020). The core reason many physicians move outside Nigeria every day is the industry's lack of funding and inadequate salary compared to other developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…This unequal ratio of medical personnel to patients has led to poor quality of health care services. For example, research has recorded the low number of medical personnel to rate of mortality in Nigeria (Suleiman, Mikail, 2020). This low number is as a result of emigration of medical personnel for a better quality of life.…”
Section: Medical Personnel Brain Drain Syndrome In the Nigerian Contextmentioning
confidence: 99%
“…It was estimated that as of 2020, there were 1.2 million Nigerians in the diaspora. 4 A study in 2016 stated that brain drain leaves Nigeria behind without healthcare practitioners who have the ability to help shape public policies to rebuild the crumbling to almost non-existent healthcare infrastructure. 6 The American Medical Association reported that over 17,000 of the medical doctors practicing in the United States were born or trained in Africa.…”
Section: Introductionmentioning
confidence: 99%